Sistem Informasi Antrian Online Berbasis Web di Klinik Sahabat Padang - Junaidi, Ahmad; Wadisman, Cendra (Journal of Computer Science and Information System(JCoInS), 2022)
Utilization of Information Technology can assist clinics in improving the quality of service to patients. Friends of the clinic is an obgyn clinic in the city of Padang and is one of the clinics that has many patient visits. So far, the queuing system for patient registration at the clinic has used technology such as WhatsApp, but with this method there are several obstacles, such as (1) having to involve clinic staff to register patients to get a queue, (2) patients piling up in the waiting room to wait for services, (3) and psychologically has the potential to increase the patient's illness because of the long waiting time. This running queuing system is considered inefficient, so innovation is needed to create queuing applications that can be used by patients independently without involving clinic staff, view doctor's schedules in real time and get queue numbers automatically and queue status can be monitored by patients. With this clinic queuing system, patients will come to the clinic when they are close to the queue number they have, get service without having to queue in waiting in the clinic waiting room. By using the queuing method that is designed, it is expected that speed, accuracy, integration, service improvement, and efficiency of service to patients can be further improved.